Correlation between iron metabolism and development of breast cancer in pre- and postmenopausal women - Kubiak, Tomasz (Menopause Review/Przegląd Menopauzalny, 2013)
Nowadays an increased attention is paid to the correlations between iron metabolism and the process of carcinogenesis. However, the role of this element in the development of breast cancer depends on the period of women’s life: before or after the menopause. In menstruating women, iron deficiency anemia can contribute to the increasing level of vascular endothelial growth factor (VEGF), which is a negative predictor of breast cancer. The high level of estrogens also plays a negative role, because free radicals, generated in the cycle of estradiol metabolism, are the factor in the release of iron from ferritin. Iron unbound to protein is harmful, because it participates in the Fenton reaction, in which a highly reactive hydroxyl radical is produced. This radical is very dangerous, because it damages DNA and lipids. Cessation of menstruation after menopause reduces the loss of iron. This can lead to the body overload with this element and strengthen the process of carcinogenesis by accelerating the production of reactive oxygen species (ROS). Improper turnover of iron in the body does not have to be associated with dietary habits. Iron metabolism is strictly controlled by several proteins so as to prevent the excessive accumulation of free form of this element in the body. Ferritin, ferroportin, transferrin and its receptor play a role in tumor growth, because rapidly proliferating cells have a high demand for iron. Changes in the metabolism of this element can thus be an early symptom of the cancer in women both prior to and after menopause.